Seed storage importance and behaviour of a vulnerable species Angsana (Pterocarpus indicus Willd.) - Ridesti Rindyastuti; Febrina Artauli Siahaan (The East Java Biological Society, 2019)
Angsana (Pterocarpus indicus Willd.) is one of woody plant species listed in the IUCN red list for priority in conservation as a vulnerable species. The effective and low-cost methods of seed storage is required to support the ex-situ conservation through seedling recruitments for population improvement. This study used completely randomized factorial design with 2 factors i.e. seed storage methods (room temperature, sealed jar and cold temperature), and storage duration (1,2,3,4 and 5 months). This study used 3 replications for each treatments and 10 seeds for each replication. The result showed that the seed of P. indicus start to germinate in 5-11 days after seeding while leaf emerged in 15-13 days after seeding. Seed viabilities generally were high until 3 months of storage (up to 65%) and start to decline at 4 months of storage at 51%. Storage methods and storage duration significantly influenced the seedling growth, viability, and Relative Growth Rate (RGR). There was an interaction between two factors. The storage at room temperature during a month (1RT) has the highest seedling height. The seeds stored in sealed jar during 5 months (5SJ) showed the highest seedling RGR, while the seeds stored in sealed jar during 3 months (3SJ) has the highest seed viability. For longer term storage, the seed of P. indicus should be stored in sealed jar or at room temperature at 11% moisture content. Both in the rainy and dry season, seedling recruitments were low and sapling stage was rare which showed low seedling establishment. Moreover, based on the phenological information, it is better to store the seed during the rainy season.